Women's social representations in relation to police assistance provided in living domestic violence situations - Gomes, Iracema Costa Ribeiro (2020)
The objective was to analyze the social representations of women in situation of domestic violence on police assistance. This is a qualitative research, based on the Theory of Social Representations, held in a Southwestern municipality of Bahia. The collection took place between July and November 2017 through the Free Word Association of Technique, analyzed with the aid of EVOC software, version 2005, and semi-structured interview based on the Content Analysis Technique. It was found that the social representations of women in situations of domestic violence on police assistance are anchored in experiences filled with fear, insecurity, embarrassment, seeking legal protection and punishment of the aggressor. It was observed that the police assistance offered to women in situations of domestic violence does not include their experiences, showing the need for redesign of the structure, organization and relationships established in police assistance